Comparing diversity of the terrestrial mammal communities inhabiting native forests and exotic plantations in southern Chile - Colihueque, Nelson; Vidal, Víctor; Vásquez, Contanza; Gantz, Alberto (Neotropical biology and conservation, 2023)
The mammal community of the Coastal Range of southern Chile has been little studied even though they inhabit an environment under severe threats due to anthropic disturbance. During the spring-summer seasons of 2020–2021 and 2021–2022, we characterized the communities of wild terrestrial mammals in a native forest (NF) and an exotic plantation of Eucalyptus (PL) of the Coastal Range of Osorno province by phototrapping. We used 1,060 camera-trap days in the NF and 960 camera-trap days in the PL to explore the effect of habitat type on wild mammal diversity in two localities (L-1 and L-2). We quantified the species richness, abundance, community similarity and daily distribution of mammal communities. Species richness was higher in the NF (7–8 spp) than in the PL (3–4 spp). Two community similarity index (CSI) was significantly higher between native forests (CSI = 0.728 ± 0.088) than between Eucalyptus plantations (CSI = 0.211 ± 0.097) (95% CI). Mean abundance was also higher in the NF than in the PL (L-1: 0.011 vs. 0.004 occurrence/camera-trap day (OCT); L-2: 0.008 vs. 0.004 OCT). In L-1, the most abundant mammals in the NF were Leopardus guigna (45.3% of relative occurrence (RO)) and Pudu puda (18.9% RO), and in the PL, they were Lycalopex culpaeus (50% RO) and L. guigna (37.5% RO). In L-2, the highest abundances in the NF were for P. puda (34.5% RO) and Puma concolor (27.6% RO), while in the PL, P. puda was predominant (66.7% RO). In NF of both localities, 22.2% of melanic L. guigna individuals were observed. The highest frequency of occurrences in both locations was between 12:00 and 23:59 hours, with 60% and 76.9% of detections, respectively. The species richness found in native forest is in accordance with studies carried out in other temperate rainforests of southern Chile. In addition, native forests support a richer and more similar community of terrestrial mammals than exotic forest plantations, which indicates that native forests are the main habitat for most mammals detected and that exotic plantations function as a complementary habitat for some species.